The combined role of PET/CT metabolic parameters and inflammatory markers in detecting extensive disease in small cell lung cancer - Hu, Yao; Sun, Jin; Li, Danming; Li, Yangyang; Li, Tiannv; Hu, Yuxiao (Frontiers in Oncology, 2022)
The combined role of inflammatory markers [including neutrophil/lymphocyte ratio (NLR)，platelet/lymphocyte ratio (PLR)， monocyte/lymphocyte ratio (MLR) and systemic immune-inflammation index (SII)] and PET/CT metabolic parameters [including maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), metabolic tumor volume (MTV), TLG (total lesion glycolysis)] at baseline, in evaluating the binary stage (extensive-stage disease (ED) and limited-stage disease (LD)) of small cell lung cancer (SCLC) is unclear. In this study, we verified that high metabolic parameters and inflammatory markers were related to the binary stage of SCLC patients, respectively (P < 0.05). High inflammatory markers were also associated with high MTV and TLG in patients with SCLC (P < 0.005). Moreover, the incidences of co-high metabolic parameters and inflammatory markers were higher in ED-SCLC (P <0.05) than those in LD-SCLC. Univariate logistic regression analysis demonstrated that the Co-high MTV/NLR, Co-high MTV/MLR, Co-high MTV/SII, Co-high TLG/NLR, Co-high TLG/MLR and Co-high TLG/SII were significantly related to the binary stage of SCLC patients (P=0.00). However, only Co-high MTV/MLR was identified as an independent predictor for ED-SCLC (odds ratio: 8.67, 95% confidence interval CI: 3.51-21.42, P = 0.000). Our results suggest that Co-high metabolic parameters and inflammatory markers could be of help for predicting ED-SCLC at baseline. Together, these preliminary findings may provide new ideas for more accurate staging of SCLC.